2022
DOI: 10.3389/fnut.2022.1069714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of lactic acid bacteria fermentation on quality, aroma, and metabolites of chickpea milk

Abstract: Legumes are an attractive choice for developing new products since their health benefits. Fermentation can effectively improve the quality of soymilk. This study evaluated the impact of Lactobacillus plantarum fermentation on the physicochemical parameters, vitamins, organic acids, aroma substances, and metabolites of chickpea milk. The lactic acid bacteria (LAB) fermentation improved the color, antioxidant properties, total phenolic content, total flavonoid content, lactic acid content, and vitamin B6 content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Based on Figure 5C , it can be observed that a total of 26 benzenoid compounds were detected during the fermentation process, with 12 exhibiting an increasing trend and 14 showing a decreasing trend. Among them, benzylformate — which exhibits a strong floral aroma with hints of fruit and European blackberry — showed relatively stable levels throughout fermentation (ranging from 3.71 ± 0.02 to 3.72 ± 0.05) ( 15 ). 4-Ethylphenol, a compound with a pleasant aroma that is used in coffee and other fragrances — also showed a relatively stable content after fermentation (varying from 4.19 ± 0.02 to 4.18 ± 0.03).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Figure 5C , it can be observed that a total of 26 benzenoid compounds were detected during the fermentation process, with 12 exhibiting an increasing trend and 14 showing a decreasing trend. Among them, benzylformate — which exhibits a strong floral aroma with hints of fruit and European blackberry — showed relatively stable levels throughout fermentation (ranging from 3.71 ± 0.02 to 3.72 ± 0.05) ( 15 ). 4-Ethylphenol, a compound with a pleasant aroma that is used in coffee and other fragrances — also showed a relatively stable content after fermentation (varying from 4.19 ± 0.02 to 4.18 ± 0.03).…”
Section: Resultsmentioning
confidence: 99%
“…4-Ethylphenol, a compound with a pleasant aroma that is used in coffee and other fragrances — also showed a relatively stable content after fermentation (varying from 4.19 ± 0.02 to 4.18 ± 0.03). The content of phenylacetaldehyde, which emits a floral scent reminiscent of hyacinths with undertones of almond and cherry fragrance ( 15 ), was 4.88 ± 0.02. Another key compound detected was vanillin, which possesses a strong fragrance of vanilla pods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the measurement of starch and total protein content, the seed Pei samples were first dried. The total protein content was determined using the spectrophotometric method according to the National Standards of the People's Republic of China GB/T 5009.5-2016 (Zhang et al, 2022 ). The starch content was determined according to the National Standards of the People's Republic of China GB/T 5009.9-2003, with specific procedures referenced from a previous study (Liu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The hydrolysis of glucosides of soy-based products using β-glucosidase increased their bioavailability, resulting in changed aroma profiles that impart fruity and creamy characteristics [132] Soymilk Lactobacillus plantarum 70810…”
Section: Lactobacillus Plantarummentioning
confidence: 99%